Econometric modelling of long run relationships in the Singapore currency futures market - SEQUEIRA, J. M. (Institutional Knowledge at Singapore Management University, 1997)
The paper investigates the existence of long-run relationships among settlement prices of the three major currency futures, namely Duetsche Mark, Japanese Yen and British Pound, in the currency futures market of the Singapore International Monetary Exchange. Tests of cointegration and vector autoregressive relationships among the variables are conducted. The stationarity property of each series is tested using the augmented Dickey-Fuller test, from which it is found that each of the series is non-stationary. A cointegrating relationship among settlement prices is examined for the underlying long-run economic relationships. Cointegration tests and vector autoregressive models of the rates of return were unable to establish any long-run relationships among the variables. Thus, there is no empirical evidence, in general, indicating that long-run relationships exist among the settlement prices for individual currency futures in Singapore.